2020
DOI: 10.2807/1560-7917.es.2020.25.11.2000266
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular findings during SARS-CoV-2 infection: the first case study in Finland, January to February 2020

Abstract: The first case of coronavirus disease (COVID-19) in Finland was confirmed on 29 January 2020. No secondary cases were detected. We describe the clinical picture and laboratory findings 3–23 days since the first symptoms. The SARS-CoV-2/Finland/1/2020 virus strain was isolated, the genome showing a single nucleotide substitution to the reference strain from Wuhan. Neutralising antibody response appeared within 9 days along with specific IgM and IgG response, targeting particularly nucleocapsid and spike protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
307
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 277 publications
(320 citation statements)
references
References 21 publications
10
307
0
3
Order By: Relevance
“…We did not detect any symptomatic secondary cases of COVID-19 among the 389 non-household contacts who completed active monitoring, including 77 HCP contacts and 67 community contacts from whom respiratory samples were tested for SARS-CoV-2. This finding is similar to findings from early contact investigations in Europe and Asia, [13][14][15][16] but in contrast to other data suggesting a much higher secondary attack rate. 17 It is possible that asymptomatic secondary cases could have developed in persons from whom respiratory samples were not collected, 18,19 or that secondary cases could have developed without being detected in respiratory samples (for instance, if the timing of shedding did not align with the timing of sample collection); 11 follow-up serology could help to rule out some of these possibilities.…”
Section: Discussionsupporting
confidence: 91%
“…We did not detect any symptomatic secondary cases of COVID-19 among the 389 non-household contacts who completed active monitoring, including 77 HCP contacts and 67 community contacts from whom respiratory samples were tested for SARS-CoV-2. This finding is similar to findings from early contact investigations in Europe and Asia, [13][14][15][16] but in contrast to other data suggesting a much higher secondary attack rate. 17 It is possible that asymptomatic secondary cases could have developed in persons from whom respiratory samples were not collected, 18,19 or that secondary cases could have developed without being detected in respiratory samples (for instance, if the timing of shedding did not align with the timing of sample collection); 11 follow-up serology could help to rule out some of these possibilities.…”
Section: Discussionsupporting
confidence: 91%
“…However, IgG response was detected when this case was isolated in the hospital along with a positive PCR result. Haveri et al [13] reported a patient with mild symptoms seroconverting (IgG) to SARS-CoV-2 in 9 days after onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Overall specificities were 91.9% and 73.0% for IgG and IgA ELISAs, respectively. Of 39 coronavirus disease patients, 13 were IgG and IgA positive and 11 IgA alone at sampling. IgGs and IgAs were respectively detected at a median of 12 and 11 days after symptom onset.…”
mentioning
confidence: 99%
“…The authors demonstrated neutralising antibody response appeared within 9 days, along with specific IgM and IgG response, targeting particularly N and S proteins. 30 In a large study in China, enzyme immune assays, western blots and serum neutralisation assays were used to investigate immune responses to recombinant SARS-CoV-2 nucleoprotein (NP) and S protein receptor-binding domain (RBD) in 23 patients. An increase was noted in IgG or IgM antibody levels against NP or RBD for most patients at 10 days or later after symptom onset.…”
Section: Serological Assaysmentioning
confidence: 99%